The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1074/jbc.m409996200
|View full text |Cite
|
Sign up to set email alerts
|

NO Reduction by Nitric-oxide Reductase from Denitrifying Bacterium Pseudomonas aeruginosa

Abstract: Nitric-oxide reductase (NOR) of a denitrifying bacterium catalyzes NO reduction to N 2 O at the binuclear catalytic center consisting of high spin heme b 3 and non-heme Fe B . The structures of the reaction intermediates in the single turnover of the NO reduction by NOR from Pseudomonas aeruginosa were investigated using optical absorption and EPR spectroscopies combined with an originally designed freeze-quench device. In the EPR spectrum of the sample, in which the fully reduced NOR was mixed with an NO solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 61 publications
(74 reference statements)
1
90
3
Order By: Relevance
“…This means that reaction schemes involving such electron redistribution before NO binding (such as in Ref. 19) are incompatible with our data. A simplified reaction scheme consistent with the data obtained in this study is shown in Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…This means that reaction schemes involving such electron redistribution before NO binding (such as in Ref. 19) are incompatible with our data. A simplified reaction scheme consistent with the data obtained in this study is shown in Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…It should be noted that we do not expect the binding of NO to Fe B to give rise to any significant absorbance changes at the wavelengths used, so Fe B might bind NO faster than the heme b 3 , or it could bind NO during the 200-ms mixing time, with CO still bound to the heme b 3 . Such simultaneous binding of CO to heme b 3 and NO to Fe B has been suggested previously (19). The second NO molecule could also bind to the intermediate formed at heme b 3 upon binding of the first (21).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…58 One signal, at g = 4, is consistent with a non-heme S = 3/2 {FeNO} 7 species, and another at g = 2.01, with a pronounced 3-line hyperfine structure, is characteristic of a heme S = 1/2 {FeNO} 7 system. Shiro and coworkers estimate that these two nitrosyl signals represent 30% of the total diiron site concentration.…”
Section: Spectroscopic Studies Of No Reactions With Normentioning
confidence: 89%
“…57 Also, rapid-freeze quench samples from single turnover reactions in cNOR have revealed EPR signals consistent with the trapping of S = 1/2 low-spin heme {FeNO} 7 and S = 3/2 non-heme {FeNO} 7 species. 58 …”
Section: Trans-mechanismmentioning
confidence: 99%